A Mouse Model of Acute and Chronic Pancreatitis. Issue 4 (25th April 2022) - Minaga, Kosuke; Watanabe, Tomohiro; Kamata, Ken; Kudo, Masatoshi; Strober, Warren
Abstract: Pancreatitis occurs in two forms defined by its chronicity. Acute pancreatitis (AP) occurs suddenly and only lasts for several days. Consequently, most patients with AP recover without permanent damage to the pancreas, and about 20% of patients with AP have severe disease. In contrast, chronic pancreatitis (CP) is a long‐lasting inflammation that causes permanent damage to pancreatic tissue; consequently, this form is marked by the emergence of persistent endocrine and exocrine pancreatic insufficiency. Despite these differences, AP and CP share central mechanisms of disease: in both forms, inflammation is initiated and/or sustained by the intrapancreatic activation of pancreatic digestive enzymes followed by the autodigestion of pancreatic tissues. In addition, in both forms enzymatic damage is accompanied by changes in intestinal permeability and entry of commensal organisms into the pancreas where they elicit innate immune responses that ultimately dominate and define pancreatic inflammation. In the murine models of AP and CP described here, both of these elements of pancreatitis pathogenesis are taken into account. Thus, in one approach mice are administered high doses of cerulein, a cholecystokinin analog with the ability at this dose to induce excessive activation of the cholecystokinin receptor expressed in pancreatic acinar cells and the release of active trypsin that causes both direct and indirect acinar damages due to entry of commensal organisms and stimulation of innate immune responses. In a second approach mice are administered low doses of cerulein, which causes little or no damage to the pancreas unless given along with nucleotide‐binding oligomerization domain 1 (NOD1) ligand, which in the presence of low‐dose cerulein administration induces a pathologic innate immune response mediated by NOD1. These approaches are adopted to produce AP when cerulein or cerulein plus NOD1 ligand is applied only once or to produce CP when a similar regimen is applied multiple times. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Cerulein‐induced acute pancreatitis Alternate Protocol 1 : Acute pancreatitis induced by cerulein and NOD1 ligand Basic Protocol 2 : Cerulein‐induced chronic pancreatitis Alternate Protocol 2 : Chronic pancreatitis induced by cerulein and NOD1 ligand Support Protocol : Isolation of pancreatic mononuclear cells